Pengembangan Media Pembelajaran Teks Eksplanasi Berbantuan Aplikasi VN untuk Meningkatkan HOTS Siswa Kelas XI di Mas Proyek Univa Medan - Sakinah, Nurul; Ali, Ali; Kartika, Rika (Medan Resource Center, 2024)
This study aimed to develop and assess the feasibility of learning media assisted by the VN application for identifying information in explanatory texts in class XI MIPA-1 MAS at Univa Project Medan, based on evaluations from media and material experts. The student population included classes XI MIPA-1, XI MIPA-2, and XI IIS, with data collected through questionnaires and interviews. Utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research indicated that the VN application-based learning media effectively facilitated information identification in the explanatory texts, meeting feasibility criteria. Media experts rated the validity at 94%, while material experts rated it at 86%. Teachers' evaluation averaged at 92%, and students responded positively with an average score of 93%. In conclusion, the VN application-supported learning media for identifying information in explanatory texts is valid and suitable for classroom use in class XI MIPA-1 MAS at Univa Project Medan.